José Carlos Castañeda Reyes, Señoras y esclavas. El papel de la mujer en la historia social del antiguo Egipto, México, El Colegio de México, 2008. - Torres Falcón, Marta (Estudios de Asia y África, 2010)
José Carlos Castañeda Reyes, Señoras y esclavas. El papel de la mujer en la historia social del antiguo Egipto, México, El Colegio de México, 2008.